2006
DOI: 10.1007/s10600-006-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

Components of the aerial part of Peganum harmala

Abstract: The genus Peganum (Peganaceae) is represented in the flora of the CIS by the two species P. harmala L. (wild rue) and P. nigellastrum Bge. This genus is broadly represented by wild rue in Kazakhstan [1][2][3]. Various parts of the plant are used in folk medicine to treat several illnesses [4]. Researchers from various countries have been studying the chemical composition of this plant since 1841 because of its therapeutic importance [5][6][7][8][9][10][11][12][13]. Mainly the alkaloid composition is studied. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1-Hentetracontanol, alcohols, were found in a large number of studies on phytoconstituents. For example Agedilova et al (2006) found that the aerial part of Peganum harmala, an important ethnic Chinese medicine, contained 1-Hentetracontanol. The volatile oil of hawthorn leaves has antiproliferative and apoptosis-inducing effects, and Yang et al (2015a) found the presence of 1-Hentetracontanol when their components were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…1-Hentetracontanol, alcohols, were found in a large number of studies on phytoconstituents. For example Agedilova et al (2006) found that the aerial part of Peganum harmala, an important ethnic Chinese medicine, contained 1-Hentetracontanol. The volatile oil of hawthorn leaves has antiproliferative and apoptosis-inducing effects, and Yang et al (2015a) found the presence of 1-Hentetracontanol when their components were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that a wide spectrum of beneficial and toxicological effects of P. harmala is attributed to the presence of many bioactive compounds: fixed oils [13,14] saponins [15], polyphenols [8] and alkaloids which are the major compound with up of 10% of the total seeds dry weight. These alkaloids are mainly comprised of β-carboline and quinazoline derivatives, including Harman, Harmine, Harmaline [16], Peganine and Desoxypeganine [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of P. harmala has been investigated since the 1970s [2,11]. Macro-and microelements content which can have a direct impact on pharmacological activities of medicinal plants [12], are also a key to understand many diseases [3].…”
Section: Introductionmentioning
confidence: 99%